Patient characteristics and opioid use prior to discharge after open gynecologic surgery in an enhanced recovery after surgery (ERAS) program - Hillman, R. Tyler (Gynecol Oncol, 2019)
OBJECTIVE. To identify clinical and demographic characteristics associated with the absence of opioid usage on the day before discharge among patients undergoing open gynecologic surgery within an enhanced recovery after surgery (ERAS) program. METHODS. This was a single institution retrospective cohort study including all patients who underwent elective open gynecologic surgery as part of an ERAS program between November 1, 2014 and September 30, 2018 and who were discharged between post-operative day 2 and 7. Patients were excluded if they reported preexisting chronic opioid use or underwent total pelvic exenteration. Descriptive statistics were used and multivariable logistic regression was used to identify factors associated with the absence of opioid usage on the day before discharge, after adjustment for relevant covariates. RESULTS. A total of 971 were included with a median length of stay of 3 days, and of these 526 (54.2%) used opioids on day before discharge and 445 (45.8%) did not. Absence of opioid use on the day before discharge was associated with age (P < .001), race (P = .04), Charlson Co-morbidity Index (P < .001), marital status (P = .004), and smoking status (P = .002) by univariate analysis. In a multivariable model, older age (adjusted OR 1.04; 95% CI 1.02–1.06; P < .001), current smoker status (adjusted OR 0.42; 95% CI 0.20–0.81; P = .01), and white or Caucasian race (adjusted OR 0.59; 95% CI 0.38–0.91; P = .02) were significantly associated with the absence of opioid use on the day prior to discharge. CONCLUSIONS. Nearly half of patients undergoing open gynecologic surgery within an established ERAS program did not consume any opioids on day before discharge. Safe, evidence-based reductions in post-operative opioid prescribing may be feasible for a subset of gynecologic surgery patients.